Role of science research in Agricultural Transformation - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Chief Forngueh Alangeh R.C., Chairman of CAADP Non-State Actors Coordination, talks on the importance of AASW6 in line with the role Science research plays in Agricultural Transformation The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/